Decoupling and driving forces of industrial carbon emission in a coastal city of Zhuhai, China - Jing-Chun Feng; Xue-Lan Zeng; Zhi Yu; Yong Bian; Wei-Chi Li; Yi Wang (Energy Reports, 2019)
To explore effective schemes of reducing carbon emission at the city level, this study evaluate the decoupling situation and the driving forces of industrial carbon emission in a coastal city of Zhuhai, China. Macro and micro analyses of evolutions of energy consumption, carbon emission, and industrial added value were conducted from 2006 to 2016. Carbon emission was decomposed at the overall and subdivided industrial level by using the logarithmic mean division index method (LMDI) method. Results showed that the industrial added value emerges sustainable increase tendency. Both energy consumption and carbon emission keeps continuous increase during the 11th five year period (11-FYP). They firstly decrease and then they present volatile change during the rest years of the 12-FYP. Rigorous incentives should be enacted to avoid the phenomenon of carbon emission increase rebound during the later phase of each FYP. There are no decoupling signals during the whole 11-FYP. Strong decoupling started to emerge during the 12-FYP. On a micro level, the decoupling phenomenon enhanced with the extension of the evaluation cycle. Furthermore, the economic output value is the main driving force factor of carbon emission, and the energy intensity effect is the dominant driver for reducing the industrial carbon emission during the 11-FYP. For the 12-FYP, the conjunctive role of the industrial structure effect, the energy intensity effect, the energy mix effect, and carbon emission factor effect drives carbon emission mitigation.
Keywords: 330; Carbon emission; City-level; Decoupling; Driving forces; Energy consumption; Industrial sector